An improved temperature dependent analytical model to predict AlGaN/GaN high electron mobility transistors AC characteristics. (18th July 2019) - Khan, Mohammad N.; Ahmed, Umer F.; Ahmed, Muhammad M.; Rehman, Saif
Abstract: In this paper, an improved temperature dependent model has been presented to predict AC characteristics of submicron AlGaN/GaN high electron mobility transistors (HEMTs). The model evaluates effects of channel temperature on the device AC intrinsic parameters. It has been shown that the rise of channel temperature is almost linear in nature, and it depends upon both the ambient temperature as well as on the operating voltages of the device. By reassessing two dimensional electron gas (2‐DEG) carrier concentration, n s, high electron mobility transistor (HEMT)'s analytical I − V equations for both linear as well as saturation regions have been modified. The modeled DC characteristics showed a good degree of accuracy with the experimental data. By evaluating temperature and bias dependent charge accumulation in the depletion region of the device, an AC model for the device intrinsic parameters has been developed. S‐parameters of the device have been evaluated by using the modeled AC intrinsic parameters that showed a good agreement with the measured data. Thus, the developed technique could be a useful tool to predict AC parameters of submicron AlGaN/GaN HEMTs meant for harsh environments.